2013
DOI: 10.1017/s0016672313000189
|View full text |Cite
|
Sign up to set email alerts
|

Variant at 9p21 rs1333049 is associated with age of onset of coronary artery disease in a Western Indian population: a case control association study

Abstract: The 9p21 chromosomal region has been associated with coronary artery disease (CAD) in many genome wide association studies (GWAS). To date no information exists regarding the rs1333039 SNP which showed the strongest association in the WTCCC GWAS with CAD risk in the Indian population. The present study attempts to replicate the findings in the Indian population. Genotyping for rs1333049 was done in 229 cases and 151 controls by allele-specific real-time assay. A higher frequency of the risk allele rs1333049C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The result of our study confirmed that the rs1333049 is significantly associated with CAD in the Tanzanian population, which is in agreement with the findings in other ethnic (7,8,13,(32)(33)(34)(35)(36)(37), although a weak association was reported in some populations (38,39). Our results showed not only the rs1333049 CC genotype, but also that the C allelic form is associated with CAD congruent with the results from some populations in Europe and Asia (7,8,13,(33)(34)(35)(36)(37) though G allelic form was associated with CAD in some populations (Cakmak et al 2015). In addition, our results also confirmed the significant associations of rs2383206, rs2383207, rs10757274 and rs10757278 located on chromosome 9p21.3 with the risk of CAD as reported in multiple populations (7,8,15,16,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 92%
“…The result of our study confirmed that the rs1333049 is significantly associated with CAD in the Tanzanian population, which is in agreement with the findings in other ethnic (7,8,13,(32)(33)(34)(35)(36)(37), although a weak association was reported in some populations (38,39). Our results showed not only the rs1333049 CC genotype, but also that the C allelic form is associated with CAD congruent with the results from some populations in Europe and Asia (7,8,13,(33)(34)(35)(36)(37) though G allelic form was associated with CAD in some populations (Cakmak et al 2015). In addition, our results also confirmed the significant associations of rs2383206, rs2383207, rs10757274 and rs10757278 located on chromosome 9p21.3 with the risk of CAD as reported in multiple populations (7,8,15,16,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 92%
“…A positive risk association in the subjects above 40 years of age was seen in the study with the mutant genotype having an OR=5.506 with a highly significant p < 0.001 (Table 2). However, Bhanushali et al (2013) reported the SNP to be robustly associated with premature or Sex and age specific associations 5 the early onset CAD which is also supported by the results of Meng et al (2008), Ellis et al (2010) and the association was supported by meta-analysis study done by Palomaki et al (2010). But in present study, no mutant in the CAD patients was found below 40 years of age in the pre-specified subgroup analysis based on age.…”
Section: Discussionsupporting
confidence: 81%
“…Only two studies report data on rs1333049 C/G and CAD risk in West and North Indian populations. (Bhanushali, et al, 2013) recruited 229 CAD patients and 136 controls from West India and revealed an association towards CAD with an OR=2.460, 95% CI=1.139-5.314 and 4 Kaur et al p=0.022). Kashyap et al (2018) in their study on North Indian population reported risk for both the allelic and genotypic frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The current study results were also supported by a study conducted on 100 cases of CAD and 150 controls of Indo European descent from Maharashtra in Western India. They found no significant differences in the frequency of the IL-6 -174G > C genotypes between cases and controls [ 21 ].…”
Section: Discussionmentioning
confidence: 99%